Letter from Charles Henry Locke, Arlington Heights, District of Columbia, to his brother John Locke, Dublin, informing him that his regiment, Company H New Jersey Zouaves, are within sight of the city of Washington - Locke, Charles Henry; Locke, John, fl. 1860-1863 (1863)
Writes: "I write to let you know the number of my regiment I belong to Company H New Jersey Zouaves within sight of the city of Washington. Napsacks and all ready for four days march. An awful load to carry. I can't get a chance to get into town to send my bounty to my family. I am now a caged bird and feel uneasy with money in my pocket amongst so many thieves."
Keywords: United States. -- Army; United States -- History -- Civil War, 1861-1865